Pendampingan Pengembangan Rencana Strategis BUMDesa Di Desa Kemasantani Kecamatan Gondang Kabupaten Mojokerto - Nekky Rahmiyati; Achmad Yanu Alif Fianto (AMMA : Jurnal Pengabdian Masyarakat, 2023)
This community service activity aims to assist Kemasantani Village in developing a Strategic Plan for Village-Owned Enterprises (BUMDesa). BUMDesa is a business entity that has the potential to drive the village economy and utilize village assets to create added value and develop a digital economic ecosystem. This activity includes assistance in preparing the BUMDesa Strategic Plan for the next five years, with a focus on operational aspects of BUMDesa and increasing revenue. The main objective is to ensure that BUMDesa in Kemasantani Village can operate efficiently, increase community income, and strengthen local economic resilience. The service team works together with the Kemasantani Village community to develop a sustainable strategic plan, implement BUMDesa development planning methods, and provide the necessary support to develop BUMDesa in the area. This activity is a manifestation of the team's concern for supporting village economic development and improving the quality of life of local residents.